Biorefinery process for hydrothermal liquefaction of microalgae powered by a concentrating solar plant: A conceptual study. (15th December 2017) - Giaconia, Alberto; Caputo, Giampaolo; Ienna, Antonio; Mazzei, Domenico; Schiavo, Benedetto; Scialdone, Onofrio; Galia, Alessandro
Graphical abstract: Highlights: A concentrating solar plant drives the hydrothermal liquefaction of microalgae. Conventional chemical units can be coupled with solar heat. Costs of the solar plant marginally affect the cost of biocrude. Proposed strategy seems promising to store solar energy in biofuels. Abstract: A conceptual analysis of coupling a concentrating solar power plant with a biorefinery process consisting in the hydrothermal liquefaction (HTL) of microalgae to biocrude was performed. The configuration of the CSP-HTL plant was designed to allow continuous operation considering 10 kT of microalgae processed each year using, for the first time, a ternary nitrate mixture as heat transfer fluid and storage medium in the temperature range of 340–410 °C. With adopted models, the capital and operating costs of the solar plant marginally affect the minimum fuel selling prize (MFSP) of biocrude that decreases with the size of the solar field and of the thermal storage system provided that the scale of CS plant is large enough. A MFSP of the biocrude of 2.19 US$/kg was estimated that is quite similar to that reported in the literature for more conventional processes of HTL of microalgae with capability similar to that considered in this study. This value for the MFSP is lower than that calculated for the same HTL plant in which part of the produced biocrude is used as bio-fuel to drive the process. These results indicate that the utilization of solar heat in an indirect solar reactor could be an interesting option to improve sustainability of the processes and to store solar energy in biofuels.